A German version of the GOHAI - Hassel AJ, Rolko C, Koke U, Leisen J, Rammelsberg P. (Blackwell Synergy, 2008)
Translation, reliability analysis and validation of a German version of the Geriatric/General Oral Health Assessment Index (GOHAI) was the aim of this study.